PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY DALAM PENGGUNAAN KARTU TELKOMSEL - Rahmi Meutia; Muhammad Fauzi Arkan (Departemen Manajemen, Universitas Syiah Kuala, 2018)
This aims for this study is to determine the effect of Relationship Marketing (including financial benefits, social benefits and structural ties) partially and simultaneously to Customer Loyalty using Telkomsel for Samudra University Students. This is of quantitative research using purposive sampling technique with 100 respondents with multiple linear regression analysis for data analysis. Hypothesis testing is carried out through partial test (t test), simultaneous test (F test) and test coefficient of determination (R2). From the data analysis obtained regression equation Y = 2,015 + 0,162X1 + 0,301X2 + 0,393X3 + e. Partially (within t test analysis) and simultaneously (within F test analysis) Relationship Marketing variables have a significant effect on Customer Loyalty for using Telkomsel simcards to Universitas Samudra Students. Analysis of coefficient determination shows financial benefits, social benefits and structural ties influence 53.2% customer loyalty for using Telkomsel simcards at Universitas Samudra students, while the remaining 46.8% is influenced by other variables not examined in this study. KeywordsRelationship Marketing, Customer Loyalty